Polarization-dependent YVO4 crystal Raman laser operation with 816 and 890 cm−1 shifts. (December 2021) - Duan, Yanmin; Sun, Yinglu; Zhu, Haiyong; Li, Zhihong; Zhang, Li; Zhang, Ge
Highlights: Polarization-dependent YVO4 crystal Raman laser operations were demonstrated. Both first Stokes waves at 1184 and 1194 nm based on 816 and 890 cm −1 shifts were achieved. Over watt level and 16% conversion efficiency for Raman laser with 816 cm −1 shift was achieved. Abstract: Polarization-dependent YVO4 crystal Raman laser operations for both X(ZZ)X and X(YY)X Raman configurations were demonstrated. An optical anisotropy Nd:YAP crystal was used as the laser crystal for polarized fundamental laser oscillation. Both first Stokes waves at 1184 nm and 1194 nm converted from 1080 nm were realized based on 816 cm −1 shift in X(YY)X Raman configuration and 890 cm −1 shift in X(ZZ)X Raman configuration, respectively. The maximum average output power of 1.18 W and the conversion efficiency of 16.3% for main output spectrum of 1183.7 nm and average output power of 1.09 W and the conversion efficiency of 15.1% for single output spectrum of 1194.4 nm were achieved with both Raman configurations, respectively. The results show that make full use of the polarization characteristics of YVO4 crystal and its different Raman shifts, the polarized laser output with different Stokes wavelengths could be realized.